KALMAN FILTER Q-R EMPIRICAL OPTIMIZATION (مجلة البحوث الأكاديمية, 2026)
In this paper, in order to simplify the application of the Kalman filter in practice, and as a continuation to the work presented in [14], the Kalman filter empirical optimization is redone from the design parameters point of view, which are the variances of the input disturbance Q and the output measurement error R, where, for a range of Q and R values, the optimal Kalman filter performance is determined empirically also for the specified process parameters and conditions.  Furthermore, from the last step, a three dimensional graph of the optimal Kalman filter gain versus Q-R is constructed and presented as a normalized general solution to Kalman filter optimal innovation gain, also, the normalized graph can be put and used as general solution in table format.